Farnesoid X receptor (FXR): Structures and ligands - Jiang, Longying; Zhang, Huajun; Xiao, Desheng; Wei, Hudie; Chen, Yongheng (Computational and structural biotechnology journal, 2021)
[Display omitted] Farnesoid X receptor (FXR) is a bile acid activated nuclear receptor (BAR) and is mainly expressed in the liver and intestine. Upon ligand binding, FXR regulates key genes involved in the metabolic process of bile acid synthesis, transport and reabsorption and is also involved in the metabolism of carbohydrates and lipids. Because of its important functions, FXR is considered as a promising drug target for the therapy of bile acid-related liver diseases. With the approval of obeticholic acid (OCA) as the first small molecule to target FXR, many other small molecules are being evaluated in clinical trials. This review summarizes the structures of FXR, especially its ligand binding domain, and the development of small molecules (including agonists and antagonists) targeting FXR.